2023
DOI: 10.25259/sni_162_2023
|View full text |Cite
|
Sign up to set email alerts
|

Virtual neurosurgery anatomy laboratory: A collaborative and remote education experience in the metaverse

Abstract: Background: Advances in computer sciences, including novel 3-dimensional rendering techniques, have enabled the creation of cloud-based virtual reality (VR) interfaces, making real-time peer-to-peer interaction possible even from remote locations. This study addresses the potential use of this technology for microsurgery anatomy education. Methods: Digital specimens were created using multiple photogrammetry techniques and imported into a virtual simulated neuroanatomy dissection laboratory. A VR education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 27 publications
(41 reference statements)
0
14
0
Order By: Relevance
“…Photogrammetry has gained increased attention in the neurosurgical community reflected by an increasing number of publications using professional DSLR cameras, 13 smartphonebased photogrammetry, 7,10 or endoscope camera scanning for deep corridors. 3 However, the methods have mainly been developed to model anatomy from cadaver 3,[6][7][8]10,13,14 with sparse experience on the application of the method to create 3D models based on intraoperative images. One study of Nicolosi et al described generation of intraoperative 3D models with very good quality.…”
Section: Discussionmentioning
confidence: 99%
“…Photogrammetry has gained increased attention in the neurosurgical community reflected by an increasing number of publications using professional DSLR cameras, 13 smartphonebased photogrammetry, 7,10 or endoscope camera scanning for deep corridors. 3 However, the methods have mainly been developed to model anatomy from cadaver 3,[6][7][8]10,13,14 with sparse experience on the application of the method to create 3D models based on intraoperative images. One study of Nicolosi et al described generation of intraoperative 3D models with very good quality.…”
Section: Discussionmentioning
confidence: 99%
“…For neurosurgeons, brain tumor surgery presents complex challenges due to a delicate tradeoff between removing as much neoplastic tissue as possible and minimizing the loss of brain function [4]. To achieve this successfully, there has to be very low threshold for errors [21]. Likewise, the armamentarium of operative tools for neurosurgeons has evolved tremendously to address such safety concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, the Oculus Quest 2 is a VR system that consists of an HMD and two handheld touch controllers equipped with sensors. Here, the user is fully immersed in a virtual space and can interact with virtual objects in simulated environments, using controllers [20,21]. This standalone system relies on internet connectivity to access the cloud-based Holoeyes XR platform.…”
Section: Outline Of Trial With Mixed Reality Modelsmentioning
confidence: 99%
“…It was our pleasure to read the interesting article by Gonzalez-Romo et al .,[ 4 ] who assessed an immersive virtual reality (VR) platform for neurosurgery residents’ anatomy understanding. It was shown that this method could be promising for enhancing trainees’ learning experience and could be proven a valuable educational tool.…”
mentioning
confidence: 99%
“…Thus, although we certainly believe that the study by Gonzalez-Romo et al . [ 4 ] is very interesting and could enable researchers to further explore the value of immersive VR, the literature so far has shown that its effectiveness is not superior to that of conventional neuroanatomy education methods, although 3D visualization could be potentially helpful. We consider that this study may certainly attract future researchers’ interest to investigate if the positive residents’ opinions will be accompanied by learning effectiveness.…”
mentioning
confidence: 99%